SOME DIRECTIONS IN THE MODIFICATION OF AZOLES - Ibrayev M.K.; Takibayeva A.T.; Fazylov S.D.; Rakhimberlinova Zh.B.; Issabayeva M.B.; KelmyaleneA.A. (Academic Scientific Journal of Chemistry, 2020)
This article presents studies on the targeted search for new derivatives of azoles, such as benzthiazole, 3,5-dimethylpyrazole, 1,3,4-oxadiazole-2-thione, 1,3,4-thiadiazole. The possibility of combining in one molecule of the azole ring with other cyclic compounds: the alkaloid cytisine, morpholine, furan and some arenes has been studied. To obtain new compounds, the reactions of bromination, acylation, and interaction with isothiocyanates were studied. Optimal synthesis conditions were studied for all reactions. It was found that the reaction of 4-bromo3,5-dimethylpyrazole with isothiocyanates, in contrast to the previously written derivatives of anilines, takes a longer time and requires heating the reaction mixture. The combination of a pirasol fragment with halide substituents often results in an enhanced therapeutic effect. The synthesized 2-bromine-N-(6-rodanbenzo[d]thiazole-2-yl)acetamide, due to the alkylbromide group, is an important synth in the synthesis of new benzthiazole derivatives. Its derivatives combine in one molecule the rest of rhodanbenzthiazole with alkaloid cytisine and biogenic amine morpholine and are potentially biologically active compounds, since the molecule structure contains several pharmacophoric fragments: benzthiazole and alkaloid (amine) heterocycles, rhodane and urea groups. The mechanism of formation of 1,3,4-oxadiazole-2-tyons from hydrazides under action on them by carbon disulfide was studied and assumed. It was shown that dithiocarbamates in acidic medium decompose with the release of hydrogen sulfide and the formation of highly reactive isothiocyanate group. Then, intra-molecular cyclization occurs, with the formation of end products - 1,3,4-oxadiazole-2-thions. The structures of the synthesized compounds were studied by 1 H and 13C NMR spectroscopy. All synthesized substances are potentially biologically active compounds, since they contain several pharmacophore fragments in their structure.